Sud'ba millionera v Rossii . Fate of a Millionaire in Russia - Vasilieva, Irina (Studio Fishka Film, 2005)
Verzio FF Submission The protagonist of this film is a talented financier who became a millionaire in the early 1990s, a leap that ended with eight years of imprisonment in a Siberian prison. Upon his release, he is faced with a very different country. The film follows a convicted millionaire’s encounter with the new realities of Putin’s Russia.